Comparison of Einstein-Boltzmann solvers for testing general relativity - Bellini, E; Barreira, A; Frusciante, N; Hu, B; Peirone, S; Raveri, M; Zumalacárregui, M; Avilez-Lopez, A; Ballardini, M; Battye, R; Bolliet, B; Calabrese, E; et al. (American Physical Society, 2018)
We compare Einstein-Boltzmann solvers that include modifications to General Relativity and find that, for a wide range of models and parameters, they agree to a high level of precision. We look at three general purpose codes that primarily model general scalar-tensor theories, three codes that model Jordan-Brans-Dicke (JBD) gravity, a code that models f(R) gravity, a code that models covariant Galileons, a code that models Hořava-Lifschitz gravity and two codes that model non-local models of gravity. Comparing predictions of the angular power spectrum of the cosmic microwave background and the power spectrum of dark matter for a suite of different models, we find agreement at the sub-percent level. This means that this suite of Einstein-Boltzmann solvers is now sufficiently accurate for precision constraints on cosmological and gravitational parameters.